Intellectual Concepts of Skepticism in Industrial Product Design: مصعب حسن عبد-شيماء عبد الجبار (Al-Academy, 2021)
The industrial design occupies an important status in public and private life activities, because it contains a group of interactive, productive, and interconnected institutions, which is confirmed by Descartes who is credited for promoting the method of skepticism on sound foundations, showing that in order for us to search for the truth, we must suspect everything that we confront let it be once in our life time, especially our options in the scientific research and industrial design and product, starting from the knowledge heritage and the intellectual concepts that ascend to the levels of the functional, aesthetic and environmental performance, the significance of skepticism becomes clear. The research problem lies in this question: Do the foundations of skepticism enable the industrial designer to reframe the design idea aesthetically and functionally? The research aims to find a relation between the concepts of the skepticism and the intellectual values of the industrial designer. That was the most prominent part in chapter one. As for the second chapter, it consists of two sections. The first is titled skepticism conceptually. The second section is concerned with the orientations of Cartesian skepticism and its reflections on the designer and the industrial product. The third chapter consists of the research procedures, that the content analysis method has been adopted in order to achieve the research objectives. The research community consists of the products (floating car, bracelet telephone, ring telephone) manufactured in Germany. The most important results have been reached at in chapter four including:1- The relation between the Cartesian skepticism and the technical values indicates three-dimensional perceptions of floating products from the world of imagination, illusion and fantasy.2- The problem of functional suitability is considered one of the fundamental considerations taken in designing the industrial product and according to the results, a number of conclusions have been reached at the most important of which are:1- The products lacked the ability to compete with similar products in focusing on the aesthetic perspective, whereas the performative one, as a partial substitute in the product design structure.2- Mathematical encryption algorithms are considered the most important systems for skepticism treatment in the design system.